Santa Maria Antiqua: The Amalgamation of Identity in Early Medieval Rome - Cayce Davis (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
The intent of this investigation is to frame an identity for the church of Santa Maria Antiqua and the urban condition of Rome during the sixth through eighth centuries. Coupling topographical and semiotic information with larger geographic issues, this study interrogates the church and specific individuals associated with it as a way of more comprehensively understanding Santa Maria Antiqua as a visual medium of cultural change and political propaganda. Narrating the complex formation of personal and social identity at the site allows us to understand greater physical and social contexts and explore more thoroughly early Christian Rome.